Arabic Language As A Medium Of Academic Instruction: A Specialist Perspective/ اللغة العربية أداة التدريس في الجامعة من وجهة نظر المختصين - Basil Faisal Al-Zu’bi; Hashim Saleh Manna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Language is a part of society's identity and is required in all aspects of life, especially education. The importance of this study comes from the fact that Arabic is growingly global and that on the national level, it serves the progress and provides national integrity. The research follows the descriptive method in theoretical studies, while the practical application depends on electronic interviews and the evaluation of experiences or opinions of the respondents in essay forms. The research will show the value of Arabic as a means of education, especially at the university level, the availability of modern technology in teaching, and improving the Arabic language teaching methods. Moreover, the research advises teaching all fields of knowledge by using the Arabic language and enabling the Arabic language assemblies, particularly in translating various terminology into Arabic.